A new species of Opilioacarus With, 1902 (Acari: Opilioacaridae) from Italy, and a new diagnosis of the genus - De Araujo, Marcel Santos; Di Palma, Antonella; Fazzio Feres, Reinaldo Jose [UNESP] (Magnolia Press, 2018)
No living Opilioacarus species have been described from Europe for more than a century since the first finding and species description in the early twentieth century. Using the material deposited in Museo Civico di Storia Naturale of Verona, Italy, it was possible to identify and describe a new Opilioacarus species and review the genus diagnosis, using the shape of setae d and setation of the preanal segment. The new species is also briefly compared with the other Opilioacarus species; Opilioacarus italicus (With, 1904) is considered a nomen dubium.
Keywords: Opilioacarida; epigean; free-living; soil; Palearctic